2022
DOI: 10.1002/rth2.12831
|View full text |Cite
|
Sign up to set email alerts
|

Extended‐duration thromboprophylaxis for abdominopelvic surgery: Development and evaluation of a risk‐stratified patient decision aid to facilitate shared decision making

Abstract: Background Extended‐duration thromboprophylaxis is used to decrease risk of venous thromboembolism (VTE) after surgery but may increase the risk of bleeding. The decision to complete a course of extended‐duration thromboprophylaxis can be challenging. Objective The objective of this study was to develop an acceptable patient decision aid (PtDA) to facilitate shared decision making for the use of extended‐duration thromboprophylaxis following major abdominal surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
2
0
0
Order By: Relevance
“…Guest et al performed a similar analysis and concluded that twelve is a sufficient sample size for interview studies assessed for emergent themes [ 14 ]. Results from our alpha testing were similar to other decision aids developed using the Ottawa template [ 17 , 18 , 19 , 20 ]. Ivankovic et al developed and alpha tested their decision aid on extended thromboprophylaxis following major pelvic surgery in 2022 [ 20 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Guest et al performed a similar analysis and concluded that twelve is a sufficient sample size for interview studies assessed for emergent themes [ 14 ]. Results from our alpha testing were similar to other decision aids developed using the Ottawa template [ 17 , 18 , 19 , 20 ]. Ivankovic et al developed and alpha tested their decision aid on extended thromboprophylaxis following major pelvic surgery in 2022 [ 20 ].…”
Section: Discussionsupporting
confidence: 67%
“…Results from our alpha testing were similar to other decision aids developed using the Ottawa template [ 17 , 18 , 19 , 20 ]. Ivankovic et al developed and alpha tested their decision aid on extended thromboprophylaxis following major pelvic surgery in 2022 [ 20 ]. Physician feedback was split (50/50) in terms of the length of the decision aid and the amount of information contained.…”
Section: Discussionsupporting
confidence: 67%